2004
DOI: 10.1016/j.ejca.2004.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of thymidylate synthase expression in the signet ring cell histotype component of colorectal carcinoma

Abstract: Thymidylate Synthase (TS) is the key enzyme for DNA synthesis pathways and is inhibited by 5-fluorouracil (5FU). The aim of this work was to study TS expression and the proliferation rate in the different histological types of colorectal carcinoma (CRC). 50 patients with CRC were included in this study and evaluated immunohistochemically using the monoclonal antibodies, TS106 and Ki67. 20 tumours were of the intestinal type, 15 cases were signet ring cell carcinoma (SRCCs) and 15 cases were "mixed-type", with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…Surgical management has a key role in the treatment of localized tumors. [42,46]. The effectiveness of targeted therapies including angiogenesis inhibitors and EGFR inhibitors is not established.…”
Section: Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Surgical management has a key role in the treatment of localized tumors. [42,46]. The effectiveness of targeted therapies including angiogenesis inhibitors and EGFR inhibitors is not established.…”
Section: Treatmentmentioning
confidence: 98%
“…The aim of the treatment is to improve symptoms, maintain quality of life, and stop tumor progression. Published series showed that these SRCC are less sensitive to commonly used chemotherapy drugs, including 5FU, oxaliplatin, and irinotecan[7,46,47].Cabibi et al have demonstrated that this drug resistance may be due to a low proliferative activity of tumor cells, as the analysis of 15 SRCC samples showed very low levels of Ki-67 expression (a proliferation marker) and weak positivity for thymidylate synthase (key enzyme for DNA synthesis pathways targeted by 5FU)…”
mentioning
confidence: 96%
“…MMP-9 which located on cell surface is needed for tumor invasion and angiogenesis 19 . The increasing of MMP-2 could degrade extracellular matrix and destroy protein on basalis membrane; thus, tumor cell could enter the stroma and adjacent tissue easier 20 . MT1-MMP (membrane-type MMPs) activate pro-MMP-2 and break type I, II, III collagens, gelatine, fibronectin, laminin-1, vitronectin, cartilage proteoglycans, and fibrillin-1, which expressed by epithelial cell 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the application of other therapeutic approaches has been increasing, including chemotherapy 10 . However, relevant researches have shown that colorectal SRCC is relatively insensitive to the commonly applied chemotherapeutics, such as irinotecan, oxaliplatin as well as 5-fluorouracil 13 , 14 , 23 . Cabibi et al have demonstrated that such drug resistance may be due to a low proliferative activity of tumor cells, as the analysis of 15 SRCC samples showed very low levels of Ki-67 expression (a proliferation marker) and weak positivity for thymidylate synthase (key enzyme for DNA synthesis pathways targeted by 5-FU) 13 , 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%